Asymmetric monetary policy rules for the euro area and the US - Junior Maih; Falk Mazelis; Roberto Motto; Annukka Ristiniemi (European Central Bank (ECB), 2021)
We analyse the implications of asymmetric monetary policy rules by estimating Markovswitching DSGE models for the euro area (EA) and the US. The estimations show that until mid-2014 the ECB's response to in ation was more forceful when in ation was above 2% than below 2%. Since then, the ECB's policy can be characterised as symmetric, and we quantify the macroeconomic implications of this policy change. We uncover asymmetries also in the Fed's policy, which has responded more strongly in times of crisis. We compute an optimal simple rule for the EA and the US in an environment with the effective lower bound and a low neutral real rate, and find that it prescribes a stronger response to in ation and the output gap when in ation is below target compared to when it is above target. We document its stabilisation properties had this optimal rule been implemented over the last two decades.
Keywords: E52; E58; E31; E32; 330; Inflation targeting; Markov-switching DSGE; optimal monetary policy; effective lower bound; Bayesian Estimation